The psychological experience of integrating content and language - Talbot, Kyle R. 1988-; Gruber, Marie-Theres 1987-; Nishida, Rieko 1972- (Psychology of language learning and teaching, 2021)
This book explores the psychology of teaching and learning a subject through a second or other language. It highlights the challenges and benefits of teaching and learning in integrated content and language settings and covers themes such as identity, self-concept, cognition, beliefs, well-being, interventions and professional development